Total Pancreatectomy and Islet Autotransplantation in a Child with Recurrent Pancreatitis - Grützmann, Robert; Ludwig, B.; Weitz, J.; Ludwig, S. (Zentralblatt für Chirurgie, 2016)
Hereditary pancreatitis in children is rare. The indications for surgery in these children are complications and severe pain that cannot be managed by conservative treatment. Surgical treatment options are duodenum preserving resections as well as drainage procedures. Recurrences are common following theses surgical procedures, because usually the whole pancreas is affected. The majority of the children with symptomatic hereditary pancreatitis are free of pain after total pancreatectomy. When total pancreatectomy is combined with islet autotransplantation, pancreoprivic diabetes can be attenuated or even prevented. The principle of spleen-preserving total pancreatectomy combined with subsequent islet autotransplantation is shown in a case of a 10-year-old child with chronic recurrent pancreatitis in this video.Symptomatic chronic hereditary pancreatitis in children.Spleen-preserving total pancreatectomy, reconstruction with hepatico-jejunostomy and duodeno-jejunostomy, islet autotransplantation via portal vein.If the surgeon has appropriate experience, spleen-preserving total pancreatectomy is a safe procedure. In combination with islet autotransplantation, it may attenuate or prevent diabetes mellitus associated with total pancreatectomy. In highly selected pediatric patients, this surgical procedure has a major benefit compared to a purely symptomatic therapy.
EVALuna2:15256